The Impact of Remittances on Children's Education in Jungkat Village, Mempawah Regency - Afnan Triyuning Andini; Antonia Sasap Abao; Annisa Rizqa Alamri; Grace Destiani Sanda (SOSHUM : Jurnal Sosial dan Humaniora, 2023)
The income of Indonesian workers sent to their families in their hometown will affect changes in the economic conditions of the families of Indonesian workers in terms of education. This study aims to determine the effect of remittances made by Indonesian workers who work abroad on the education of their family members in the area of origin. This study aimed to determine whether Indonesian workers who work abroad are aware of the importance of using remittances as the fee for their family education. As education is a basic need and benefits the improvement of the education of the nation's children. This research used qualitative research methods with data taken from Jungkat Village, Mempawah Regency. This study showed that most Indonesian workers in the village work to earn a living and provide appropriate education to their family members. In addition, remittances allow families in their hometowns to easily receive the salary given by Indonesian workers abroad. However, there are also disadvantages for those Indonesian workers who send remittances, as families and communities do not know each other that well.